Regulating Infrastructure: The Impact on Risk and Investment - Guthrie, Graeme (Journal of Economic Literature, 2006)
The last thirty years have witnessed a fundamental change in the regulation of infrastructure industries. Whereas firms were subject to rate of return regulation and protected from entry in the past, they now face various forms of incentive regulation, competition is actively promoted by many regulators, and both regulators and the firms they regulate must often confront rapid technological progress. This paper surveys the literature on the investment implications of different regulatory schemes, highlighting the relevance of modern investment theory, which puts risk and intertemporal issues, such as the irreversibility of much infrastructure investment, center stage. It discusses the impact on regulated monopolists' investment behavior of key regulatory characteristics, namely the price flexibility allowed by the regulator, the length of the regulatory cycle, and the costs the regulator will allow the firm to recover at future regulatory hearings. It also considers the impact of competition, especially the situation where a vertically integrated firm has its operation of a bottleneck asset regulated, on investment by regulated firms and their competitors.